THE ROLE OF SONGS IN TEACHING LISTENING - Olimjonova , Madina; Salikhova , Nasiba (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Listening is one of the most essential yet challenging skills in foreign language learning. Students often experience difficulties in understanding spoken English due to fast speech, unfamiliar pronunciation, and limited vocabulary. Modern teaching approaches emphasize the importance of using interactive and motivating techniques in the classroom. One of the most effective tools is the integration of songs into listening lessons. Songs provide authentic language input, improve pronunciation, and create a positive learning atmosphere. This article discusses the pedagogical value of songs and their role in enhancing students’ listening comprehension skills.